Serum IL-17A in Behçet’s disease - Emiroglu, Nazan; Cengiz, Fatma Pelin; Erdem, Gul Bahar (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction : Behçet’s disease is a chronic multisystem disease with spontaneous remissions and relapses. Several studies show that autoimmune mechanisms play an important role in the development of Behçet’s disease. Activation of T cells and neutrophils is important in the pathogenesis of the disease. Interleukin 17 (IL-17) is a new cytokine that induces several types of cells to secrete proinflammatory cytokines in many inflammatory and autoimmune diseases. Aim : This study evaluated the serum levels of IL-17A in active and stable Behçet’s disease patients. Material and methods : Seventy-six patients who had active clinic findings of Behçet’s disease were enrolled in our study. Seventy age- and sex-matched controls were also enrolled. Serum IL-17 levels were studied in peripheral venous blood samples. Results : No significant differences were found between active Behçet’s disease patients and controls in terms of serum IL-17A (p > 0.05). Conclusions : These results suggest that IL-17A serum levels do not play an important role in active Behçet’s disease.